Francesca Ciancimino Howell, Food, Festival and Religion: Materiality and Place in Italy - Frascaroli, Fabrizio (Journal for the Study of Religion, Nature and Culture, 2021)
Francesca Ciancimino Howell, Food, Festival and Religion: Materiality and Place in Italy (London and New York: Bloomsbury Academic, 2018), 224 pp., 114.00 (hbk), ISBN: 978-1-3500-2086-3.